2016
DOI: 10.1111/anae.13571
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline in the elderly after surgery and anaesthesia: results from the Oxford Project to Investigate Memory and Ageing (OPTIMA) cohort

Abstract: SummaryConcerns have been raised about the effects on cognition of anaesthesia for surgery, especially in elderly people. We recorded cognitive decline in a cohort of 394 people (198 women) with median (IQR) age at recruitment of 72.6 (66.6–77.8) years, of whom 109 had moderate or major surgery during a median (IQR) follow‐up of 4.1 (2.0–7.6) years. Cognitive decline was more rapid in people who on recruitment were: older, p = 0.0003; male, p = 0.027; had worse cognition, p < 0.0001; or carried the ε4 allele o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 40 publications
(61 reference statements)
2
33
1
Order By: Relevance
“…Cognitive scores are commonly expressed as z-scores, which denote how many standard deviations are between a given score and the mean value of a set of scores derived from reference data. Prior studies have examined cognitive trajectories before and after surgery and anaesthesia, 7,16,17 but systematic, repeated assessments of cognitive trajectories, as conducted in the present study, have not been used to study the long-term consequences of anaesthesia and surgery on cognition.…”
mentioning
confidence: 99%
“…Cognitive scores are commonly expressed as z-scores, which denote how many standard deviations are between a given score and the mean value of a set of scores derived from reference data. Prior studies have examined cognitive trajectories before and after surgery and anaesthesia, 7,16,17 but systematic, repeated assessments of cognitive trajectories, as conducted in the present study, have not been used to study the long-term consequences of anaesthesia and surgery on cognition.…”
mentioning
confidence: 99%
“…Despite the rise to cultural supremacy of the randomised controlled trial as the preferred study design for assessing the effects of interventions, researchers continue to conduct, and journals continue to publish, retrospectively collected data. For instance, in the last few months, Anaesthesia has published two such papers , the second being accompanied by an editorial by Doherty and Shenkin revisiting Bradford Hill's criteria for determining causation in associations in scientific findings. This is worth re‐reading with the paper of Stein et al in mind.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Prior studies have suggested that approximately 16% of elderly patients over the age of 70 years old have mild cognitively impairment (1,2). According to the U.S. Preventative Service Task Force, cognitive function is not routinely assessed either pre-operatively or post-operatively, with increasing cognitive decline after surgery (3,4). Therefore, given the paucity of data on the effects of CI and associated surgical risks, surgeons face challenging clinical decisions operating on a rapidly aging population (5).…”
Section: Introductionmentioning
confidence: 99%